Case Report: Severe osteoporosis misunderstood by bone metastasis after total gastrectomy and multiple metastasectomy - Hwang, Seong Ho; Kim, Dong Jin (Frontiers in Oncology, 2023)
After radical gastrectomy for gastric cancer, patients should be monitored from two perspectives. One is local recurrence or metastasis, and the other is nutritional and metabolic side effects. Herein, we report a case of severe osteoporosis that was misunderstood for bone metastasis due to increased bone scan and positron emission tomography-computed tomography uptake in the patient who underwent total gastrectomy and consecutive multivisceral metastasectomy. She was administered bisphosphonates, calcium carbonate, and cholecalciferol. After 3 months, a follow-up bone scan revealed decreased intensity of hot-uptake lesions, healed fracture lesions, and eventually improved bone pain. This study supports the need for careful nutritional screening as well as cancer surveillance after gastrectomy for gastric cancer and the need for screening guidelines for bone metabolic diseases.